Three Decades of Iran’s Policy of Exporting the Islamic Revolution: Politics, Ends, and Means (American Journal of Islam and Society, 2010)
Three decades after its 1979 Islamic Revolution, Iran’s foreignpolicy remains committed to “exporting the revolution” (sodoureenqelab). Through this policy, the Islamic Republic of Iran wantsto make the world safe for not only Islam and Muslims, but for alloppressed people around the world. The idea is based on the ideologyof Imam Khomeini, who presented it in a general way in hisimportant work on jurisprudence. To him, the role of Imam is topreserve the Islamic ummah’s unity, liberate the Islamic homelandfrom the seizure and influence of the colonizers and their puppetgovernments, and initiate the just Islamic government.In this article, I explore the politics, ends, and means of exportingthe revolution in the overall context of Iran’s foreign policyas well as show how the divinely inspired nature of the revolutionwas to bring Islamic justice to humanity and the variouspeaceful and coercive means it adopted to provide happiness,well-being, and salvation to all nations. To Imam Khomeini andhis followers, the final end of “great Islamic community” couldnot be achieved in the current arrogant international society withouthelping the disintegrated Muslim nations to unite with eachother and using adequate force.